2020
DOI: 10.1055/a-1179-6093
|View full text |Cite
|
Sign up to set email alerts
|

Exercise with End-expiratory Breath Holding Induces Large Increase in Stroke Volume

Abstract: Eight well-trained male cyclists participated in two testing sessions each including two sets of 10 cycle exercise bouts at 150% of maximal aerobic power. In the first session, subjects performed the exercise bouts with end-expiratory breath holding (EEBH) of maximal duration. Each exercise bout started at the onset of EEBH and ended at its release (mean duration: 9.6±0.9 s; range: 8.6–11.1 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 37 publications
(87 reference statements)
2
11
1
Order By: Relevance
“…BH protocols lasting 3–5 weeks reported performance gains of 3%–4% related to two acute mechanisms: increased stroke volume (up to 30%) and haemoglobin concentration (up to 10%; Woorons et al, 2016 ; Lapointe et al, 2020 ; Woorons et al, 2020 ). These ergogenic benefits are likely due to increased left ventricular stroke volume ( Woorons et al, 2021b ) and post-BH spleen contraction ( Inoue et al, 2013 ). Only one study was found that examined the acute effects of BH during running ( Woorons et al, 2021a ).…”
Section: Breath Toolsmentioning
confidence: 99%
“…BH protocols lasting 3–5 weeks reported performance gains of 3%–4% related to two acute mechanisms: increased stroke volume (up to 30%) and haemoglobin concentration (up to 10%; Woorons et al, 2016 ; Lapointe et al, 2020 ; Woorons et al, 2020 ). These ergogenic benefits are likely due to increased left ventricular stroke volume ( Woorons et al, 2021b ) and post-BH spleen contraction ( Inoue et al, 2013 ). Only one study was found that examined the acute effects of BH during running ( Woorons et al, 2021a ).…”
Section: Breath Toolsmentioning
confidence: 99%
“…19 These authors attributed the augmented oxygen uptake to a greater stroke volume which may be the consequence of the large ventricular filling and the "pump effect" that occur at the end or just after each bout of end-expiratory breath holding. 16,17,33 This central adaptation assumption was recently reinforced by the larger muscle re-oxygenation observed during the recovery periods of a RSA test without concomitant greater oxygen extraction following four weeks of RSH-VHL in basketball players. 21 Considering that in the present study the SpO 2 levels recorded during training in RSH-VHL were similar to those of the previous studies, it is likely that the physiological adaptations were also similar.…”
Section: Discussionmentioning
confidence: 96%
“…However, previous literature has reported some enhancement of molecular actors involved in glycolysis with RSH [ 7 , 52 ]. RSH with voluntary hypoventilation at low lung volume due to the hypercapnic effect also promotes significant effects on blood lactate concentration and stroke volume [ 18 , 54 ]. Finally, a significant impact of training was observed concerning minute ventilation and RER suggesting that RST may induce changes in muscle metaboreflex and chemoreflex activation [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%